2020
DOI: 10.1111/ajt.16212
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 in lung transplant patients: A case series

Abstract: Several case reports and small case series have been published on coronavirus disease 2019 infection after solid organ transplantation; however, thus far there are limited data on coronavirus disease 2019 infections in lung transplant patients. In the present single‐center case series we discuss 10 lung transplant patients with a documented severe acute respiratory syndrome coronavirus 2 infection, diagnosed with nasopharyngeal swab in 8 and bronchoalveolar lavage in 2. Eight of 10 patients needed hospital adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 17 publications
2
41
0
Order By: Relevance
“…Although early considerations judged transplant recipients to be more prone to severe courses of COVID‐19 due to their chronically immune‐incompetent state, there are also considerations that immunosuppression might be protective against fatal disease 23 . The inflammatory response to SARS‐CoV‐2 might be attenuated in transplant recipients 8,24 and their risk for mortality due to COVID‐19 does not seem to be excessively increased 15,25,26 . This was supported by the results of our present study, with a majority of survey participants reporting favorable courses in LTx recipients.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Although early considerations judged transplant recipients to be more prone to severe courses of COVID‐19 due to their chronically immune‐incompetent state, there are also considerations that immunosuppression might be protective against fatal disease 23 . The inflammatory response to SARS‐CoV‐2 might be attenuated in transplant recipients 8,24 and their risk for mortality due to COVID‐19 does not seem to be excessively increased 15,25,26 . This was supported by the results of our present study, with a majority of survey participants reporting favorable courses in LTx recipients.…”
Section: Discussionsupporting
confidence: 81%
“…The COVID‐19 pandemic rapidly spread worldwide in early 2020 and the first cases of COVID‐19 in LTx recipients have already been reported from centers all over the world 7–15 . Due to their generally increased vulnerability to viral infections, immunocompromised patients were considered to be at high risk for critical courses of COVID‐19.…”
Section: Discussionmentioning
confidence: 99%
“…To be included, the study must have reported clinical data on adult (A-CA) or pediatric (P-CA) cancer patients and SOT or HCT recipients with confirmed COVID-19. Our inclusion and exclusion criteria identified 64 SOT studies, 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 11 HCT studies,…”
Section: Methodsmentioning
confidence: 99%
“…Mortality ranged from 9 to 46% with most in the 18–30% range depending on the cohort and circumstances 14,15,17,33,72,73,75,77‐79,83‐85,88,89,91,94,95,103,104 . All‐cause mortality during the study period of the UK registry reached 26% for SOT recipients and 10% for those on the waitlist, although local utilization decisions related to resource availability may have impacted these numbers 74 .…”
Section: Epidemiology and Outcomesmentioning
confidence: 99%